СЕЗОННЫЕ ИЗМЕНЕНИЯ ЭЛЕМЕНТНОГО СОСТАВА ВОДЫ РЕКИ АМУДАРЬИ - Жумамуратов, М.А. (SCIENCE and SOCIETY, 2019)
The author of the article discusses seasonal variations in the chemical composition of water samples from the Amudarya delta. As a result of neutron activation analysis of water samples taken in each season, about 30 chemical elements were identified. In winter, pollution increased in a result of flushing and irrigation waters into the collector and then back to the Amudarya river.
Keywords: Amu Darya river; water; neutron activation analysis; chemical composition; winter; autumn; spring; summer; micro elements; river waters; collector waters